Speed regulation enhancement for SRM drive in PHEV applications by using hybrid fuzzy logic controller - Veerendra, A. S.; Mohd Rusllim, Mohamed; M. H., Sulaiman; Peddakapu, K.; Sudhakar, K.; Sukumaran, Sreenath (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Speed regulation enhancement of a Switched Reluctance Motor (SRM) Driveby using modularfront-endintegrated multilevel converter for plug-in hybrid electric vehicle (PHEV) applications are studied and evaluated in this paper. Theoperating modes of the system are basing on Turn-On &Turn OFF of the switches in the converter circuit. In order to achievefast demagnetization and excitation, during generator driving mode, the battery bank is used to elevate the phase voltage. To get the multiple voltage responses and torque increment, an additional charging capacitor and a reframed four-level structure from the converter during battery driving mode is required. A hybrid Fuzzy Logic Controlleris proposedin orderto control the speed of the SRM motor. This paper mainly focuses on the comparison of the hybrid fuzzy logic controller with conventional P & PI and to prove the proposed controller provides the best performance and high robustness compared to a conventional P & PI controller. Matlab / Simulink is used to simulate.